Development of Smart Live Edu-Multimedia Multilingual Adaptive for Digital Quran to Children and Parents Utilize meta-Deep Lightweight SORA Algorithm - Cholissodin, Imam; Shampton, Achmad; Soebroto, Arief Andy (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
This research related to collaboration Islamic religious education methods in the family home is urgent and important, particularly for children and parents, especially regarding the introduction of the Quran as the word of Allah SWT delivered by the Prophet Muhammad SAW through the angel Gabriel. To improve education ways, the approach, if only conducted conventionally, such as only monotonous with static books, of course, is not enough to attract interest in reading to memorization. Based on these constraints, this study carried out an adaptive approach by utilizing technology from the meta-Deep lightweight SORA algorithm as a tool to create a smart digital Quran that is able to display live adaptive multilingual multimedia, including textual, audio, and video content. We propose Cooperative Agents Meta-Learning (CAML) algorithm as its contribution in supporting greater convenience for early childhood education and parents. The results of this study are expected to be able to provide a treasure trove of Islamic education with a blended method while maintaining methods such as in Islamic boarding schools with the latest Artificial Intelligence (AI) technology.